Total and partial cross sections of the ¹²С(γ,3α) reaction - Afanas’ev, S.N.; Khodyachikh, A.F. (Вопросы атомной науки и техники, 2004)
The total cross-section of the ¹²С(γ,3α) reaction in the energy range from the threshold to 40 MeV has been measured by the method using a diffusion chamber. It has been established that the two-stage mechanism is dominant: first, α-particles and a ⁸Ве nucleus are formed, then the latter disintegrates into two α-particles. Partial cross-sections of channels of forming excited states of ⁸Ве were measured.